Changes in methacholine induced bronchoconstriction with the long acting beta 2 agonist salmeterol in mild to moderate asthmatic patients. Issue 11 (November 1993) - Booth, H; Fishwick, K; Harkawat, R; Devereux, G; Hendrick, D J; Walters, E H
Abstract : BACKGROUND--Beta-2 agonists protect against non-specific bronchoconstricting agents such as methacholine, but it has been suggested that the protection afforded by long acting beta 2 agonists wanes rapidly with regular treatment. METHODS--The changes in airway responsiveness were investigated during and after eight weeks of regular treatment with salmeterol 50 micrograms twice daily in 26 adult asthmatic patients, 19 of whom were receiving maintenance inhaled corticosteroids. The study was of a randomised, placebo controlled, double blind design. Airway responsiveness to methacholine was measured as PD20 by a standardised dosimeter technique 12 hours after the first dose, at four weeks and eight weeks during treatment (12 hours after the last dose of test medication), and at 60 hours, one week and two weeks after stopping treatment. RESULTS--There were no significant differences between the baseline characteristics of the two groups. A significant improvement in PD20 was seen at all points during treatment with salmeterol compared with the placebo group, with no significant fall off with time. PD20 measurements returned to baseline values after cessation of treatment with no significant difference from the placebo group. CONCLUSIONS--Salmeterol gave significant protection against methacholine induced bronchoconstriction 12 hours after administration. This protection was of small magnitude, but there was no significant attenuation with eight weeks of regular use and no rebound increase in airway responsiveness on stopping treatment in a group of moderate asthmatic patients, the majority of whom were receiving inhaled corticosteroids.